The Impact of Nickel Downstreaming on Economic Growth in East Luwu Regency : JEL Classification: L72, O13, O14, Q32, R11 - Waode Sarmin; Nur Mita (Mustard Journal De Ecobusin, 2026)
This study analyzes the impact of nickel downstreaming on regional economic growth in East Luwu Regency, Indonesia, during the 2020–2026 period. The research aims to evaluate whether value-added industrialization associated with nickel processing contributes significantly to regional economic expansion. Using a quantitative explanatory approach, the study employs a time-series regression model based on regional economic indicators, including Gross Regional Domestic Product growth, downstreaming value added, industrial investment, government expenditure, labor absorption, and population growth. The findings reveal that nickel downstreaming has a positive and statistically significant effect on regional economic growth, primarily through increased industrial investment and expansion of mining and processing activities. However, the results also indicate that growth remains highly capital-intensive, with limited employment spillovers and increasing dependence on the nickel sector. The novelty of this study lies in its subnational focus and its integration of downstreaming indicators into a regional growth framework covering the post-export ban industrialization period. The study contributes to the literature on resource-based industrialization and provides practical implications for policymakers regarding the importance of diversification, local economic linkages, and inclusive industrial development in resource-rich regions.